Lâ€™irrigation du territoire. Chandigarh e la visione moderna del paesaggio (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
This paper discusses the role of landscape as a unifying element in the project for the city of Chandigarh. During the twentieth century the â€œclassicalâ€ idea of landscape as a visual background prevailed on the idea of landscape as a device able to tie space into infinity. The plan for the city of Chandigarth and its main spots (monuments and buildings), as the Capitol hill, are conceived as symbolic constructions in which nature comes into contact with the artificial space of the city and its institutions. This interpretation derives from the following considerations: - The evolution of the plan of Chandigarh from the early schemes by Albert Mayer to the plan by Le Corbusier that changed radically the role of the void-system into the urban space structure.- The importance attributed by Le Corbusier to the Plan dâ€™arborisation supporting the design work of a committee that cared about the planting of the trees.- The meaning of the Capitol soil (natural and artificial) and the overall narrative based on a complex metamorphosis of symbols recomposing fragments of nature and city.